2022
DOI: 10.3390/s22124549
|View full text |Cite
|
Sign up to set email alerts
|

Remaining Useful Life Prediction Method for Bearings Based on LSTM with Uncertainty Quantification

Abstract: To reduce the economic losses caused by bearing failures and prevent safety accidents, it is necessary to develop an effective method to predict the remaining useful life (RUL) of the rolling bearing. However, the degradation inside the bearing is difficult to monitor in real-time. Meanwhile, external uncertainties significantly impact bearing degradation. Therefore, this paper proposes a new bearing RUL prediction method based on long-short term memory (LSTM) with uncertainty quantification. First, a fusion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…This phenomenon is due to the fact that the intermittent impact and wear of the space cage are usually accompanied by strong fluctuation in characteristic parameters, resulting in the inaccurate prediction of RUL. The data pre-screening method based on SAE-K-medoids proposed in 15.49% 0.8670 317.9 1.3662 GRU [45] 35.32% 0.9466 147.9 0.7041 LSTM [46] 29.41% 0.9291 172.9 0.7669 Proposed approach −1.97% 0.9885 21.9 0.1106 this paper can effectively eliminate volatility and significantly improve subsequent prediction accuracy. By comparing the proposed method with cases 2, 4, 6 and 8, it can be observed that changing the type of NN can also improve prediction accuracy under the same pre-processing conditions.…”
Section: Comparison Of Prediction Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…This phenomenon is due to the fact that the intermittent impact and wear of the space cage are usually accompanied by strong fluctuation in characteristic parameters, resulting in the inaccurate prediction of RUL. The data pre-screening method based on SAE-K-medoids proposed in 15.49% 0.8670 317.9 1.3662 GRU [45] 35.32% 0.9466 147.9 0.7041 LSTM [46] 29.41% 0.9291 172.9 0.7669 Proposed approach −1.97% 0.9885 21.9 0.1106 this paper can effectively eliminate volatility and significantly improve subsequent prediction accuracy. By comparing the proposed method with cases 2, 4, 6 and 8, it can be observed that changing the type of NN can also improve prediction accuracy under the same pre-processing conditions.…”
Section: Comparison Of Prediction Methodsmentioning
confidence: 95%
“…To further validate the proposed method, it is compared with some RUL prediction models developed in recent five years [23,45,46]. Use different methods to analyze the test data, and the results are shown in table 12.…”
Section: Comparison Of Prediction Methodsmentioning
confidence: 99%
“…Lei et al [ 7 ] utilized a multi-scale dense-gate recurrent neural network to identify relevant information at different timescales to improve the performance of model. Yang et al [ 8 ] proposed an improved long-short term memory neural network to estimate bearing performance degradation. In [ 9 ], a hybrid model based on long short-term memory and Elman neural networks predicted RUL for lithium-ion batteries.…”
Section: Introductionmentioning
confidence: 99%
“…To extend the fuel-cell lifetime and reduce its maintenance cost, the management and control strategy of the PEMFC has become a hot research topic. The prognostic method provides a potential solution to extending the PEMFC lifespan [ 11 , 12 ]. As the prerequisite for the maintenance of PEMFC, an effective prognostic method can estimate the state of health (SOH) of the fuel cell and predict the system’s future evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [ 25 ] adopted a long short-term memory network (LSTM) to predict the degradation voltage, which identified the superiority of the LSTM network compared with the relevance vector machine (RVM) and the Elman network. Yang et al [ 12 ] proposed an RUL prediction method for the bearing’s degradation process based on LSTM. However, the data-based method suffers from poor generality in practical deployment and there is a shortage of training data because of the costly and time-consuming PEMFC aging test.…”
Section: Introductionmentioning
confidence: 99%